High pressure effects on U L3 x-ray absorption in partial fluorescence yield mode and single crystal x-ray diffraction in the heavy fermion compound UCd11. (15th February 2016) - Nasreen, Farzana; Antonio, Daniel; VanGennep, Derrick; Booth, Corwin H; Kothapalli, Karunakar; Bauer, Eric D; Sarrao, John L; Lavina, Barbara; Iota-Herbei, Valentin; Sinogeikin, Stanislav; Chow, Paul; Xiao, Yuming; et al.
Abstract: We report a study of high pressure x-ray absorption (XAS) performed in the partial fluorescence yield mode (PFY) at the U L3 edge (0–28.2 GPa) and single crystal x-ray diffraction (SXD) (0–20 GPa) on the UCd11 heavy fermion compound at room temperature. Under compression, the PFY-XAS results show that the white line is shifted by  +4.1(3) eV at the highest applied pressure of 28.2 GPa indicating delocalization of the 5 f electrons. The increase in full width at half maxima and decrease in relative amplitude of the white line with respect to the edge jump point towards 6 d band broadening under high pressure. A bulk modulus of K 0   =  62(1) GPa and its pressure derivative,   =  4.9(2) was determined from high pressure SXD results. Both the PFY-XAS and diffraction results do not show any sign of a structural phase transition in the applied pressure range.